Nursing Perspective of Providing Palliative Care to the Children—A Narrative Review - Agrawal, Uma Shanker; Sarin, Jyoti; Garg, Rakesh (Journal of Health and Allied Sciences NU, 2023)
Introduction Palliative care of children (PCC) is a philosophical and a structured approach to providing tailored care to children with life-threatening diseases. Understanding the role of nurses and empowering them to take up the role of palliative care nurse are imperative to strengthen these services and make the palliative care services more accessible to the patients.Method The literature search was done in two database, PubMed and Scopus, using keyword and Medical Subject Headings (MeSH) terms such as children, palliative care, end of life, hospice, bereavement, and nursing. Records were screened by authors and relevant articles were included in the review.Discussion PCC should start with the diagnosis of the illness continue through all the phases of illness. Bereavement support to the family is also a part of palliative care. Nurses are in a key position to play important role in the PCC team. Nurses play various roles such as direct care provider, communicator, patient advocate, respite nurse, and counselor.Conclusion PCC is aimed to improve the quality of life of the child and family. It is crucial to achieving universal health coverage. Role of nurse is vital in providing PCC.
Keywords: bereavement care; children; end of life care; nursing; palliative care